Signature of CEF-phonon coupling in Kondo lattice system CeCuGa3. Issue 1 (1st March 2022) - Anand, V K; Fraile, A; Adroja, D T; Sharma, Shivani; Tripathi, Rajesh; Ritter, C; de la Fuente, C; Biswas, P K; Garcia Sakai, V; del Moral, A; Strydom, A M
Abstract: We present the results of inelastic neutron scattering (INS) measurements on Kondo lattice heavy fermion CeCuGa3 . The low-temperature magnetic susceptibility exhibits an anomaly near 2.6 K associated with an antiferromagnetic transition which is further confirmed by the heat capacity measurement. The analysis of magnetic heat capacity C mag ( T ) based on the crystal electric field (CEF) model reveals an overall CEF splitting of ∼ 21 meV. The INS data reveal two strong magnetic excitations near 4.5 and 6.9 meV, which, however failed to reproduce the observed C mag ( T ). We therefore analyze the INS data by a model based on magneto-elastic (i.e. CEF-phonon) coupling which suggests that the excitations observed near 4.5 and 6.9 meV originate from the CEF-phonon coupling as observed in CeCuAl3 and CeAuAl3 .